If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x) = 3(x + 2) Remove parenthesis around (3x) 2 * 3x = 3(x + 2) Multiply 2 * 3 6x = 3(x + 2) Reorder the terms: 6x = 3(2 + x) 6x = (2 * 3 + x * 3) 6x = (6 + 3x) Solving 6x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6x + -3x = 6 + 3x + -3x Combine like terms: 6x + -3x = 3x 3x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 3x = 6 + 0 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| -5=2g-9 | | 9y-43=5(y-7) | | 8.5(x+7.8)=90.23 | | a+12=65 | | 7x+y(0)=29 | | 3w^2+20w=7 | | 3(w-3)-9=-4(-5w+6)-7w | | 11.23(75.34-3x)=120.34 | | .5+3/5= | | 16.8a-v=6v | | 15.67-23.56=34.18x | | g=100-4t | | 0.25n-1.5=0.25n-1.5 | | -7(4x-7)=-80 | | P^2-20p+84=9 | | 111.78=67.8(2.7-4x) | | 4v-12-10=-5(v+9)-(v-6) | | 48+4x=-6+30-20x | | -11.0(x+3.33)=12.7 | | 3.7x+8=1.7x+9 | | 7x+1=-4-5 | | 7-6x=1-5x | | 4x^2+3xy-y^2=1 | | 33.8=7.6-2.06x | | 5b-4b=4b-2 | | 3t^2+22t+32=0 | | -17x-20-8x-2=128 | | 4(6-b)=12 | | 30-5x=16-3x | | 60-14x= | | -5+8x=-8x+23 | | 34x*2= |